Antimicrobial activity of dermocosmetic formulations based on Piptadenia gonoacantha - Franco, Adriane Jane; Rosa, Marcelo Barcellos da; Nonato, Idelvânia dos Anjos; Oliveira, Leandro Licursi de; Caldeira, Eliana Amaro de Carvalho; Amaro, Marilane de Oliveira Fani; Almeida, Gabriel Feu Guarçoni de; Silva, Karen Vieira da; Pereira, Cassia Gondim; Carvalho, Camilo Amaro de (Ciência e Natura, 2022)
The search for herbal innovations with medicinal properties has intensified. As for this matter, the extracts of Piptadenia gonoacantha, present antimicrobial, anti-inflammatory and antinociceptive action, as well as absence of proven toxicity. The objective was to evaluate the antibacterial action of formulations containing extracts of Piptadenia gonoacantha. The extract was prepared and characterized by liquid chromatography coupled to mass spectrometry (UPLC-MS/MS). This was used for the development of cream, ointment, gel, balm and liquid soaps formulations, being submitted to evaluation, along with the extracts, for antibacterial activity. The characterization of the extract revealed the presence of rutin, ferulic acid, p-coumaric acid, quercitrin, canferol, apigenin and 6-hydroxycoumarin in their constitution. The formulations presented inhibition halos against strains of S. aureus and S. epidermides, with mean efficiency, relative to the positive control, of 47% to 99%. The best results were found for the S. epidermides strain with a mean of 91.5% efficiency in relation to the control. The presence of the metabolites observed in the characterization of the extract justifies the antibacterial action observed in its evaluation, as well as to the formulations. The formulations evaluated have promising antibacterial activity as natural therapeutic alternatives for the treatment of infectious processes.